2005
DOI: 10.1017/s0025315405012403
|View full text |Cite
|
Sign up to set email alerts
|

larval growth and mortality of japanese spanish mackerel (scomberomorus niphonius) in the central seto inland sea, japan

Abstract: Growth and mortality rates of larval Japanese Spanish mackerel (Scomberomorus niphonius) were estimated by using otolith daily increments in 1997 and 1998 in the Sea of Hiuchi, central Seto Inland Sea. There was no day^night di¡erence in the abundance and size-distribution of S. niphonius larvae in the 3^10 mm sizeclasses, indicating the larvae were e⁄ciently collected by the larva-net used for sampling (1.3 m mouth diameter, 0.5 mm mesh). Mean absolute growth rate (0.748 mm d 71 in 1997, 0.821mm d 71 in 1998)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…In previous studies, no significant relationship was observed between larval (<12 mm) and juvenile (>12 mm) abundance, whereas juvenile abundance was positively correlated with 1 yr old fish abundance in subsequent years in the 1980s (Kishida 1991) and 1990s (Shoji & Tanaka 2003). Strong year-classes occurred in years when larval growth rate was significantly high (Shoji & Tanaka 2003). Year-to-year fluctuation in mortality during the larval stage seems to be relatively large, but that between the juvenile and 1 yr old stage is small.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…In previous studies, no significant relationship was observed between larval (<12 mm) and juvenile (>12 mm) abundance, whereas juvenile abundance was positively correlated with 1 yr old fish abundance in subsequent years in the 1980s (Kishida 1991) and 1990s (Shoji & Tanaka 2003). Strong year-classes occurred in years when larval growth rate was significantly high (Shoji & Tanaka 2003). Year-to-year fluctuation in mortality during the larval stage seems to be relatively large, but that between the juvenile and 1 yr old stage is small.…”
Section: Introductionmentioning
confidence: 71%
“…Young-of-the-year Japanese Spanish mackerel inhabit the Sea of Hiuchi until December, then migrate to oceanic waters . In previous studies, no significant relationship was observed between larval (<12 mm) and juvenile (>12 mm) abundance, whereas juvenile abundance was positively correlated with 1 yr old fish abundance in subsequent years in the 1980s (Kishida 1991) and 1990s (Shoji & Tanaka 2003). Strong year-classes occurred in years when larval growth rate was significantly high (Shoji & Tanaka 2003).…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations